The goals and strategies of the great powers in Central Asia: the realism of the United States - Duarte, Paulo (2014)
The aim of this paper is to contribute to increase knowledge about a remote region of the world, but of utmost importance in the geopolitical and economic context of today: Central Asia. The central argument is that the great powers (the United States) demonstrate a predominantly economic interest (the search for energy resources) towards the region, pursuing fundamentally realistic-driven policies with regard to it.